PENGARUH STRATEGI QAR (QUESTION ANSWER RELATIONSHIP) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGERI KALIURANG 1 - Ratih Widya Utami; Sunarsih; Ari Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the influence of the Question-Answer Relationship (QAR) strategy on the reading comprehension skills of fourth-grade students at SD Negeri Kaliurang 1. The research was motivated by declining literacy trends, as evidenced by national assessment data and school-level reports, which indicated that only 35.7% of students met the Minimum Completeness Criteria in reading comprehension during the pretest phase. Using a mixed-methods sequential explanatory design, the study integrated quantitative data from pretest-posttest results with qualitative insights from observations, interviews, and documentation. Over three intervention sessions, students engaged in structured QAR phases concept introduction, modeling, independent practice, and reflection. The findings revealed a significant improvement in reading comprehension, with posttest results showing 78.6% of students achieving the minimum completeness criteria in. Qualitative analysis further highlighted enhanced metacognitive awareness, reduced reliance on teacher guidance, and improved collaborative discussion skills. These results confirm QAR’s effectiveness as a cognitive scaffold that systematically transforms students’ reading habits from passive reception to active, structured inquiry. The study contributes to literacy education by offering an evidence-based strategy aligned with the Merdeka Belajar curriculum and the “8 Profil Lulusan” framework, while also suggesting the need for differentiated instruction and further research on QAR’s applicability to digital and multimodal texts.